PENGARUH DESAIN VISUAL, INFLUENCER MARKETING, DAN NILAI EMOSIONAL TERHADAP MINAT BELI PRODUK VIRTUAL PADA GAME ONLINE MOBILE LEGENDS (Studi Kasus pada Mahasiswa Politeknik Negeri Medan) - Queen Amalani Saragih; Ika Mary Pasaribu; Muhammad Amri Nasution (Bisnis-Net, 2023)
The writing of this research motivated by the emergence of games that can be played online on various devices such as computers and smartphones. Indonesia itself is the country with the largest number of online game players in the world. One of the most played games in Indonesia is Mobile Legends. Many online game developers sell their virtual products for profit. But on the other hand, game developers must also pay attention to their virtual products in order to increase consumer purchase intention. The purpose of this study was to determine how the influence of visual design, influencer marketing, emotional value on purchase intention in virtual products in game mobile legends among Medan State Polytechnic students. To achieve these objectives, researcher used a sampling method with simple random sampling, with a total of 100 respondents. The method used is quantitative research with descriptive analysis techniques and multiple linear regression analysis. Based on the results of the study, it shows that visual design variable partially affects the purchase intention of virtual products in Mobile Legends, influencer marketing variable partially affects the purchase intention of virtual products in Mobile Legends, and emotional value variable partially affects the purchase intention of virtual products in Mobile Legends. Based on the results of simultaneous test statistical calculations, it can be concluded that visual design, influencer marketing, and emotional value have a positive and significant effect simultaneously on purchase intention of virtual products in Mobile Legends.